2010
DOI: 10.1016/j.transproceed.2009.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Variables Affecting Transfusion Requirements in Orthotopic Liver Transplantation

Abstract: Introduction and aims. Adult orthotopic liver transplantation (OLT) is associated with considerable blood product requirements. The aim of this study was to assess the ability of preoperative information to predict intraoperative red blood cell (RBC) transfusion requirements among adult liver recipients. Methods. Preoperative variables with previously demonstrated relationships to intraoperative RBC transfusion were identified from the literature: sex, age, pathology, prothrombin time (PT), factor V, hemoglobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 6 publications
1
37
0
Order By: Relevance
“…Amongst the general patient factors, the recipient's age and body surface area were identified as an independent predictors of the amount of RBCs transfused, the latter being proved in patients receiving a living donor transplant [18,19]. In addition, the impact of the severity of the disease assessed with the Child-Pugh score and Model of End-Stage Liver Disease (MELD) score was frequently studied, yielding inconsistent results.…”
Section: Recipient-related Predictors Of Blood Transfusionmentioning
confidence: 99%
“…Amongst the general patient factors, the recipient's age and body surface area were identified as an independent predictors of the amount of RBCs transfused, the latter being proved in patients receiving a living donor transplant [18,19]. In addition, the impact of the severity of the disease assessed with the Child-Pugh score and Model of End-Stage Liver Disease (MELD) score was frequently studied, yielding inconsistent results.…”
Section: Recipient-related Predictors Of Blood Transfusionmentioning
confidence: 99%
“…1 Blood transfusions are an expensive but necessary component of OLT because this surgery has historically been characterized by significant and sometimes unpredictable blood loss. [1][2][3][4][5] When the blood bank at our institution is notified that an OLT will occur, they immediately prepare 10 U of packed red blood cells (PRBCs) for the transplant recipient. 6 Although preparation of 10 U of PRBCs is a common approach in liver transplant centers, there is no standard for blood product preparation, and many centers have developed alternative approaches to massive tranfusion.…”
Section: Introductionmentioning
confidence: 99%
“…14 Many studies have investigated potential preoperative characteristics that are associated with massive blood loss and therefore necessitate massive blood transfusions in OLT. 1,[4][5][6]9,[12][13][14][16][17][18][19] Factors investigated vary by study and institution but include laboratory values of the recipient and donor, medical history of the organ donor, and recipient preoperative characteristics. Mondanlou and associates found that a transplant recipient's preoperative creatinine level of greater than 1.3 mg/dL positively correlated with massive blood transfusion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations